The involvement of the chemokine receptor CXCR2 in neutrophil recruitment in LPS-induced inflammation and in Mycobacterium avium infection - Goncalves, AS (2002)
Knockout mice for CXC receptor 2 (CXCR2) chemokine receptor were used to study the recruitment of neutrophils during acute and chronic inflammatory responses. When treated with lipopolysaccharide (LPS), either intraperitoneally or intratracheally, these animals had a significant reduction in the neutrophil recruitment in the first 24-48 h as compared with control mice. During 15 days of intraperitoneal infection by Mycobacterium avium, the knockout mice showed significantly reduced numbers of neutrophils in the peritoneal cavity as compared with the control mice. In contrast, the recruitment of neutrophils to the lungs during an aerogenic M. avium infection was not affected by the CXCR2 mutation throughout the 60 days of the study. Finally, we could not find any impact of the mutation on the mycobacterial growth of the infected animals. These findings indicate that CXCR2 may be essentially involved in acute inflammatory responses where an early and rapid recruitment of neutrophils is observed.